Inclusion of legal education in secondary and higher secondary education system in Bangladesh: An appraisal - Mahmud, S. M. Hayat; Rabbi, Md. Fajlay (Psychology, Evaluation, and Technology in Educational Research, 2024)
This abstract offers a succinct overview of a comprehensive analysis of the integration of legal education into Bangladesh’s secondary and higher secondary educational framework. It explores how teaching legal information at a young age can help pupils develop civic engagement, legal literacy, and awareness. Using qualitative approaches to analyze integration potential and difficulties, the study assesses the current condition of legal education in the curriculum. Interviews with students, instructors, legislators, and legal experts provide qualitative data that illuminates how legal education influences students’ moral and intellectual development. The study emphasizes the benefits of including legal education in the secondary and upper secondary curriculum since it fosters ethical reasoning, critical thinking, and a deeper understanding of legal topics. It also identifies obstacles to successful implementation, including problems with curriculum integration and resource limitations. The conclusions emphasize the significance of comprehensive legal education in developing responsible persons capable of navigating legal intricacies and making recommendations for improving Bangladdesh’s educational system through curriculum, teacher training, and legislative changes. These observations underline the critical role that legal education plays in developing socially conscious persons in secondary and higher secondary schools, and they greatly add to the current discourse in Bangladesh regarding education reform.